IMPLEMENTASI SISTEM MONITORING DAN MENENTUKAN UKM TERBAIK MENGGUNAKAN METODE TOPSIS: IMPLEMENTATION OF A MONITORING SYSTEM AND DETERMINING THE BEST UKM USING THE TOPSIS METHOD - Rizka Salsabila Nasution; Dahlan Abdullah; Ar Razi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Student Activity Units (SAUs) play a crucial role in developing students' potential, enhancing soft skills, and fostering a healthy competitive environment on campus. However, the performance monitoring system for SAUs at some universities is still conducted manually, which is time-consuming, labor-intensive, and prone to data inaccuracies. This study aims to design and implement a web-based UKM performance monitoring information system using the TOPSIS method as a decision-support tool for identifying the best UKMs. The research was conducted through the following stages: needs analysis, system design using the waterfall method, development, and system testing. The system is equipped with features for inputting activity data, evaluating criteria such as member activity, number of achievements, and annual activities, as well as TOPSIS calculations to obtain an objective ranking of student organizations. The implementation results show that the system functions well, facilitating administrators and campus authorities in monitoring and evaluating the performance of each student organization in real-time. Black-box testing indicates that all features function as expected. The final ranking based on TOPSIS calculations placed the Mahadasa Batalyon VII Satria Pasee Student Regiment (MENWA) as the best student organization with the highest preference score of 0.6841, followed by the Pramuka Racana Meurah Giri Ratu Nur Ilah with a score of 0.6254, and the Bidikmisi/KIP Kuliah Student Forum (Formadiksi) with a score of 0.6248. This system is expected to enhance transparency, motivation, and the quality of student activity management at one of the universities.